Dual facet passivation of silver halometallate for eco-friendly silver bismuth sulfide near IR photodetector - Sharma, Ashish; Kim, Hanjae; Kim, Gunhee; Kang, Jinhyeon; Lee, Cheong Beom; Bae, Sung Yong; Song, Hochan; Kim, Kyeounghak; Kim, Jong Hyun; Jung, In Hwan; Kang, Dong Won; Lee, Jihoon; et al. (Chemical Engineering Journal, 2023)
Ternary chalcogenide silver bismuth sulfide nanocrystals (AgBiS2 NCs) have taken great strides in the past few years to emerge as one of the better eco-friendly alternatives to compete with the prevalent toxic semiconductor materials such as lead sulfide quantum dots (PbS QDs) in the near-infrared (NIR) region. Nevertheless, their implementation in photodetectors has been scarce due to high dark current and complicated solid-state ligand exchange fabrication steps involved, resulting in a lower overall detectivity. The performance is further deemed to be stunted due to the difficulty associated with the passivation of the charge-neutral (1 0 0) facet of larger AgBiS2 NCs efficiently. In this work, we aimed to develop a mixed ‘halometallate’ ligand approach, wherein we introduce silver bromide (AgBr) as an ancillary ligand to silver iodide (AgI), passivating both (1 0 0) and (1 1 1) facets of cubic AgBiS2 solids in a facile solution-phase ligand exchange step to obtain highly dispersible colloidal ink. Decreased bond length, bond angle (Br-Ag-Br), and ionic size of [AgBr2-] anion induces less compressive strain compared to [AgI2–], culminating in higher molecular stability on the AgBiS2 surface. This dual passivation reduces the dark current to 6.01 × 10-7 A cm−2 and a high specific detectivity of 1.8 × 1012 Jones at 800 nm is achieved, comparable to ubiquitous PbS QD devices. We also demonstrate diminished in-gap carrier density population, enhanced light detection, and ultrafast microsecond response at higher wavelengths operating under high bias (-1V) photoconductive mode. This study illustrates the role of optimum surface coverage in eliminating the deleterious non-radiative recombination defect centers by introducing additional ligands in solution-processed AgBiS2 NC and the viability of the mixed ligand approach for stable eco-friendly NIR photodetectors.
Keywords: Detectivity; Dual facet passivation; Eco-friendly; Ligand exchanges; Near infrared photodetectors; Near infrared region; Near IR photodetector; Performance; Silver bismuth sulphide nanocrystal; Ternary chalcogenides; Dual facet passivation; Ecofriendly; NIR photodetectors; Silver bismuth sulfide nanocrystal